EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL SEBAGAI UPAYA MENJAGA KEBERLANGSUNGAN USAHA SIMPAN PINJAM BUMDESa (Studi Kasus di BUMDesa Sidi Amertha Desa Sangsit) - Ni Luh De Erik Trisnawati (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
The purpose of this study is to determine the suitability of the implementation of BUMDesa Sidi Amertha Desa Sangsit internal control to maintain the continuity of the savings and loan bussiness with internal control based on ERM ( Enterprise Risk Management) or Corporate Risk Management from COSO. This research use descriptive quantitative approach. Data collection techniques used in this research are surveys ( interviews and questionnaires) and documentation. The data analysis technique used in this study is descriptive, namely to describe the suitability of the implementation internal control to maintain the continuity of the savings and loan bussiness by using internal control based on ERM ( Enterprise Risk Management) or Corporate Risk Management from COSO. The result of his study show that COSO based internal ERM is not yet fully appropriate to be applied to the BUMDesa of Sidi Amertha, Sangsit Village. This is because by the components of the internal environment. Risk assessment and control activities that are not yet appropriate are applied to the BUMDesa so that they are not yet effective and efficient in their operation.